RESPON MODEL HBV DAN MODEL TANGKI TERHADAP ESTIMASI DEBIT ALIRAN DI DAS BOGOWONTO, JAWA TENGAH - Fitri Yusti Andini; Bambang Dwi Dasanto; I Putu Santikayasa (Bina Teknik Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2023)
ABSTRACT The scarcity of discharge data compared to rainfall data have driven the development of the rainfall-runoff model, such as the HBV and Tank models. This research aims to apply the rainfall-runoff model in the Bogowonto watershed and to assess the model outputs. The research consisted of two main stages: 1) model calibration and validation; 2) model evaluation which assesses the model performance based on the Nash-Sutcliffe Efficiency (NSE) index and the coefficient of determination (R2). The results showed that the pattern of the simulation discharge was in accordance with the observed discharge pattern; indicating performance of both models was good (NSE > 0.7 and R2 > 0.65). However, the performance of both models in the daily simulation, particularly at the beginning of the simulation period, is still not satisfactory as the simulated discharge does not match the observed discharge. In the next simulation period, the discharge of the model results were in accordance with the observed discharge; this means the performance of the model was better. In the monthly simulation, the performance of both models is not yet satisfactory during the wet season, but it is good during the dry season. Based on the results of the daily and monthly simulations, both models demonstrate good performance under low precipitation conditions, but their performance declines under high precipitation conditionsKeywords: Bogowonto watershed; HBV; rainfall-runoff model; simulation; tank ABSTRAKKelangkaan data debit dibandingkan data curah hujan memacu perkembangan model hujan-limpasan, seperti model HBV dan model Tangki. Tujuan penelitian ini adalah menerapkan model hujan-limpasan pada DAS Bogowonto dan menilai luaran hasil model tersebut. Penelitian ini terdiri dari dua tahap. Tahap pertama adalah kalibrasi dan validasi model. Tahap kedua mengevaluasi model, yaitu menilai kinerja model berdasarkan status indeks NSE dan nilai koefisien determinasi. Hasil penelitian menunjukkan bahwa secara umum pola debit simulasi telah sesuai dengan pola debit observasi, ini berarti kinerja kedua model adalah baik (NSE > 0,7 dan R2 > 0,65). Namun, kinerja kedua model dalam simulasi harian, khususnya pada waktu awal simulasi, masih belum baik karena debit simulasi tidak sesuai dengan debit observasi. Pada periode simulasi selanjutnya, debit hasil model telah sesuai dengan debit observasi; artinya, kinerja model telah semakin baik. Dalam simulasi bulanan, saat musim basah kinerja kedua model masih belum baik tetapi saat musim kering kinerja kedua model menunjukkan hasil yang baik. Berdasarkan hasil simulasi harian dan bulanan, kedua model menunjukkan kinerja yang baik saat hujan rendah tetapi saat hujan tinggi kinerja model mengalami penurunan.Kata Kunci: DAS Bogowonto; HBV; model hujan-limpasan; simulasi; tangki